2017
DOI: 10.1007/s00441-017-2702-0
|View full text |Cite
|
Sign up to set email alerts
|

Zebrafish as a model to study neuroblastoma development

Abstract: Neuroblastoma is a pediatric solid tumor arising from embryonic neural crest progenitor cells that normally generate the peripheral sympathetic nervous system. As such, the location of neuroblastoma tumors is correlated with the distribution of major post-ganglionic clusters throughout the sympathetic chain, with the highest incidence in the adrenal medulla or lumbar sympathetic ganglia (~65%). Neuroblastoma is an enigmatic tumor that can spontaneously regress with minimal treatment or become highly metastatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Zebrafish cancer models have accelerated the discovery of new mechanisms driving human cancers and identified new drugs for clinical trials [6]. A number of recent reviews detailing the experimental approaches for generating different leukemia [7], sarcoma [8], neuroblastoma [9], and germ-cell tumor [10] models are published elsewhere. Here, we focus on how genetically engineered zebrafish lines that specifically model pediatric and adolescent cancers, which we [11,36]) with corresponding anatomical tumor location in zebrafish are illustrated.…”
Section: Zebrafish In Cancer Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Zebrafish cancer models have accelerated the discovery of new mechanisms driving human cancers and identified new drugs for clinical trials [6]. A number of recent reviews detailing the experimental approaches for generating different leukemia [7], sarcoma [8], neuroblastoma [9], and germ-cell tumor [10] models are published elsewhere. Here, we focus on how genetically engineered zebrafish lines that specifically model pediatric and adolescent cancers, which we [11,36]) with corresponding anatomical tumor location in zebrafish are illustrated.…”
Section: Zebrafish In Cancer Researchmentioning
confidence: 99%
“…Zebrafish Models of Neuroblastoma Amplification of MYCN is observed in~20% of NBs and is associated with a poor prognosis [46]. Zebrafish models of NB are driven by targeted expression of the human MYCN gene to the developing peripheral sympathetic nervous system using the dopamine-β-hydroxylase (dβh) promoter [9]. Zebrafish models of NB with both low (17%) and high (70%) penetrance have been developed in order to detect cooperating mutations that either increase or decrease tumor burden, respectively [48,49].…”
Section: Neuroblastoma (Nb)mentioning
confidence: 99%
“…Through exhaustive comparison of the human and zebrafish genome assemblies, it was found that 82% of disease-causing human genes have at least one zebrafish ortholog ( Howe et al, 2013 ). This level of conservation has led to the development of a wide array of cancer models in zebrafish ( Casey and Stewart, 2018 ; Hason and Bartůněk, 2019 ; Casey and Stewart, 2020 ; Elliot, 2020 ). Through the years of ongoing research, the pathological similarities of cancer and preservation of the immune components have also been well established between zebrafish and humans.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, activation of the tyrosine kinase neurotrophin receptors TrkA and TrkB leads to apoptotic/differentiation neuroblast responses or to survival/proliferative effects, respectively [35,36,37]. Several animal models suitable to the study of NB differentiation and transformation have been generated, mainly centered in MYCN amplification and ALK hyperactivation [38,39]. NB cell differentiation can also be triggered in vitro by culturing NB cells in the presence of differentiation factors, such as retinoids (retinoic acid, RA), phorbol esters (phorbol 12-myristate 13-acetate, PMA), and neurotrophins (nerve growth factor, NGF; brain-derived neurotrophic factor, BDNF) [40,41].…”
Section: Neuroblastoma Cell Growth and Differentiationmentioning
confidence: 99%